Management Myths and Realities in Contemporary Business - Nsoha, Ify (2023)
This diploma thesis focuses on management myths and their impact on managers in across industries around the world. The literature review analyzes the various misperceptions from an academic perspective, seeking to form a preliminary framework within which the qualitative research functions. Myths and realities regarding Transformational Leadership, Hero Management, Innovation, Ethics, and more are didactically explained in the literature review, and then form the bedrock of the qualitative research conversations. This involves a deep exploration of the experiences of managers from diverse backgrounds and culminates in a discussion on the bigger implications these myths have for managers today and in the future.